Efficient modal sound synthesis on GPUs - Rausch, Dominik; Hentschel, Bernd; Kuhlen, Torsten (2014 IEEE VR Workshop: Sonic Interaction in Virtual Environments (SIVE), 2014)
Modal sound synthesis is a useful method to interactively generate sounds for Virtual Environments. Forces acting on objects excite modes, which then have to be accumulated to generate the output sound. Due to the high audio sampling rate, algorithms using the CPU typically can handle only a few actively sounding objects. Additionally, force excitation should be applied at a high sampling rate. We present different algorithms to compute the synthesized sound using a GPU, and compare them to CPU implementations. The GPU algorithms shows a significantly higher performance, and allows many sounding objects simultaneously.